Use of self-regulated learning strategies Among Teacher Education students: - Muwonge, Charles Magoba; Ssenyonga, Joseph; Kibedi, Henry; Schiefele, Ulrich (Elsevier Ltd, 2020)
In the present study, we conducted a latent profile analysis to identify three clusters of Teacher Education students based on their reported use of self-regulated learning strategies. The sample comprised 527 undergraduate Teacher Education students (Mean age ¼ 22 years; SD ¼ 2.20) randomly selected from seven universities in Uganda. Data were collected using the modified Motivated Strategies for Learning Questionnaire. These profiles included the following; (a) high self-regulated learners (252 students; 47.8%), (b) average self-regulated learners (209 students; 39.7%), and (c) low self-regulated learners (66 students; 12.5%) who differed significantly with respect to their motivational beliefs. Additionally, motivational beliefs significantly predicted latent profile membership. It is, therefore, important to understand such profiles’ differences among Teacher Education stu dents in order to improve on their self-regulated learning strategies. Implications of the study findings are further discussed in this paper
A latent profile analysis
Keywords: Latent profile analysis; Teacher education students; Average self-regulated learners; High self-regulated learners; Low self-regulated learners